2023
DOI: 10.1002/alz.13115
|View full text |Cite
|
Sign up to set email alerts
|

The role of PIMT in Alzheimer's disease pathogenesis: A novel hypothesis

Abstract: There are multiple theories of Alzheimer's disease pathogenesis. One major theory is that oxidation of amyloid beta (Aβ) promotes plaque deposition that directly contributes to pathology. A competing theory is that hypomethylation of DNA (due to altered one carbon metabolism) results in pathology through altered gene regulation. Herein, we propose a novel hypothesis involving L‐isoaspartyl methyltransferase (PIMT) that unifies the Aβ and DNA hypomethylation hypotheses into a single model. Importantly, the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Later, it was shown that the C‐terminal part of U1‐70K, a region with highly repetitive basic (Arg/Lys) and acidic (Asp/Glu) residues is sufficient to interact with tau from AD patients but not from other tauopathies [43] . Another intriguing link between Alzheimer's disease and U1 snRNP biogenesis resides in the role of Tgs1/PIMT in neurodegeneration [44] . This enzyme colocalizes with neurofibrillary tangles in AD patient brains, [45] suggesting that U1 snRNP biogenesis intermediates could also be trapped in cytoplasmic tau aggregates (Figure 2).…”
Section: What About Other Neurodegenerative Syndromes?mentioning
confidence: 99%
“…Later, it was shown that the C‐terminal part of U1‐70K, a region with highly repetitive basic (Arg/Lys) and acidic (Asp/Glu) residues is sufficient to interact with tau from AD patients but not from other tauopathies [43] . Another intriguing link between Alzheimer's disease and U1 snRNP biogenesis resides in the role of Tgs1/PIMT in neurodegeneration [44] . This enzyme colocalizes with neurofibrillary tangles in AD patient brains, [45] suggesting that U1 snRNP biogenesis intermediates could also be trapped in cytoplasmic tau aggregates (Figure 2).…”
Section: What About Other Neurodegenerative Syndromes?mentioning
confidence: 99%
“…Analogously, fibrils on the RBC surface, postulated to be comprised of β-amyloid and tau isoforms, are potential biomarkers for early detection of Alzheimer’s disease ( Nirmalraj et al, 2021 ). One key phenomenon in both Alzheimer’s Disease and RBC responses to hypoxia involves protein isoaspartyl-damage arising from dehydration/deamidation-triggering oxidant challenges (e.g., to structural proteins like 4.1 and band 3 in the aging RBC; to tau protein in Alzheimer’s disease), a process that is, in part, counteracted by protein L-isoaspartyl O-methyltransferase both in RBCs and neural cells ( D’Alessandro et al, 2023b ). Blood testing to classify patients was recently described using plasma tau protein 217, potentially accurately stratifying and detecting Alzheimer’s disease in a cost-effective way ( Brum et al, 2023 ).…”
Section: A Dynamic Perspective On Rbc Biomarker and Drug Targeting Po...mentioning
confidence: 99%
“…Hypermethylation can help drive carcinogenesis, autoimmune disease, and neurodegenerative disease 59 . Hypomethylation can also drive cancer, autoimmune disease 60 , and perhaps neurodegenerative disease as well 61 .…”
Section: Autoimmunity and Cancermentioning
confidence: 99%